A resveratrol oligomer, hopeaphenol suppresses virulence activity of Pectobacterium atrosepticum via the modulation of the master regulator, FlhDC - Kang, Ji Eun; Hwang, Sungmin; Yoo, Nayeon; Kim, Beom Seok; Chung, Eui-Hwan (Frontiers in Microbiology, 2022)
Pectobacterium atrosepticum (P. atrosepticum: Pba) which causes potato soft rot and blackleg is a notorious plant pathogen worldwide. Discovery of new types of antimicrobial chemicals that target specifically to virulence factors such as bacterial motility and extracellular enzymes is required for protecting crops from pathogenic infection. A transcriptomic analysis of Pba upon hopeaphenol treatment revealed that bacterial motility-related gene expression, including a master regulator flhDC genes, was significantly influenced by hopeaphenol. We further generated a double knock-out mutant of flhDC genes by CRISPR/Cas9 system and confirmed phenotypic changes in bacterial motility, transcription of extracellular enzymes, and disease development consistent with the result of wild-type treated with hopeaphenol. The hopeaphenol-treated Pba strains, wild-type, double mutant, and complemented strain were unable to secrete the enzymes in vitro, while ΔflhDC double mutant strain reduced the secretion. Thus, our study supports that FlhDC is essential for the virulence of Pba, and proposes that hopeaphenol modulates FlhDC-dependent virulence pathways, suggesting a potential of hopeaphenol as an anti-virulence agent to manage potato soft rot and blackleg diseases.